The Shoe Machinery Case and the Problem of the Good Trust - Keyes, Lucile Sheppard (Quarterly Journal of Economics, 1954)
Introduction, 287. — I. Violation of the Sherman Act by the United Shoe Machinery Corporation, 287. — II. Different doctrines and methods of dealing with the good trust, 292. — III. Definition and measurement of monopoly power or market control, 295. — IV. Conclusion, 304.